Contribution to the knowledge of planthoppers and leafhoppers of Slovenia (Hemiptera: Auchenorrhyncha) - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2004)
Some Auchenorrhyncha species that are new, endemic and less common in the fauna of Slovenia are presented, as well as their current distribution discussed. 63 species new to Slovenia are listed, so the total number of the species known increased to 483. Quartausius dalmatinus Dlabola is recognized as a younger synonym of Quartausius hamatus (Then). The host plants of Chlorita beieri Dlabola, Chlorita szelenica Dlabola, Macrosteles sardus Ribaut and Nanosius chloroticus (Melichar) have been recognized. A critical review of the checklist published in 2001 had also been made and misidentified or misinterpreted species and records revised. Forcipata forcipata (Flor) is removed from the Slovenian Auchenorrhyncha checklist.
Keywords: favna; Hemiptera; insekti; Slovenia; Slovenija; škržati